Development and validation of an instrument to assess the maturity of digital transformation in higher education institutions - Valdivia-Salazar, Carlos; Serquén, Oscar; Guevara, Laurita; Bravo-Jaico, Jessie; Alarcón, Roger; Germán, Nilton; Aquino, Janet; Maquen-Niño, Gisella Luisa Elena; Moreno Heredia, Armando (Frontiers in Education, 2025)
The research defined the objective of building and validating instruments to assess the level of maturity of digital transformation in higher education institutions (HEIs). It was based on a theoretical-methodological model that specified eight dimensions of analysis. The methodology included 7 phases: contextualization of the instruments, initial proposal, iterative review and improvement, content validation, pilot test, reliability analysis and exploratory factor analysis (EFA). The results of the pilot test, conducted with more than 100 participants, showed adequate levels of reliability and validity. The EFA found an adjusted factorial structure of the instruments, with approximate factors of 59.7% for students, 64.8% for teachers, 72.79% for administrators and 81.9% for managers, being considered acceptable and suggesting that they effectively capture the dimensions of analysis. In addition, it was observed that some items originally assigned to specific dimensions were regrouped into conceptually related factors, suggesting the need for adjustments in the initial proposals. Based on the results obtained, these instruments have the potential to be effective tools for identifying digital maturity in HEIs, providing a comprehensive diagnosis to guide strategic decisions and technology investment planning for HEIs. Future studies could be complemented with the perception of graduates and the increase of the sample.